Synchrotron radiation circular dichroism and conventional circular dichroism spectroscopy: A comparison. Issue 3 (2002) - Lees Lees, J. G. J. G.; Wallace Wallace, B. A. B. A.
Abstract : Conventional circular dichroism (cCD) spectroscopy is a valuable tool for secondary structure analyses of proteins. In recent years, it has been possible to use synchrotrons as light sources for CD, with the technique being known as Synchrotron Radiation Circular Dichroism (SRCD). In this study, the spectra of two proteins, the primarily helical myoglobin and the primarily beta‒sheet concanavalin A, have been collected on both a cCD instrument and on the SRCD at the Daresbury synchrotron and their characteristics were compared. Over the wavelength regions where both instruments are capable of making measurements (from about 300 to 175 nm) the spectra are very similar, except at the low wavelength extreme of the cCD spectra. In this region, the spectra deviate somewhat, due to the limitations of the light source intensity in the conventional instrument. The SRCD spectra extend to much lower wavelengths (160 nm). This additional low wavelength vacuum ultraviolet (VUV) data contains a large amount of extra information, including, for the first time, a number of peaks consistent with previously predicted charge transfer transitions.